Estimating drowning mortality in Tanzania: a systematic review and meta-analysis of existing data sources. Issue 5 (4th December 2018) - Sarrassat, Sophie; Mrema, Sigilbert; Tani, Kassimu; Mecrow, Thomas; Ryan, Dan; Cousens, Simon
Abstract : Background: The WHO advocates a 7-step process to enable countries to develop and implement drowning prevention strategies. We sought to assess, using existing data sources, the drowning situation in Tanzania as a first step in this process. Methods: We searched for data on causes of death in Tanzania by reviewing existing literature and global datasets and by in-country networking. Authors and institutions were then contacted to request aggregate data on drowning mortality. Site-specific drowning estimates were combined using a random effects meta-analytic approach. We also tested for evidence of variations in drowning estimates by sex and by age group. Results: We acquired partial or complete information on drowning deaths for 13 data sources. We found strong evidence for substantial variations between study sites (p<0.001). Combining population-based data, we estimated an average of 5.1 drowning deaths per 100 000 persons per year (95% CI 3.8 to 6.3). The proportions of deaths due to drowning were 0.72% (95% CI 0.55 to 0.88) and 0.94% (95% CI 0.09 to 1.78) combining population-based data and hospital-based data, respectively. Males were at greater risk than females, while both under-five children and adults aged 45 years or more were at greater risk than those aged 5–44 years. Conclusion: Our estimates of drowning burden are broadly in line with the 2016 Global Burden of Disease and the 2015 WHO Global Health Estimates. While this exercise was useful in raising the burden of drowning in Tanzania with policy makers, planning drowning prevention strategies in this country will require a better understanding of which subpopulations are at high risk.